Economic crisis in Spain (2008) (2014)
In this paper the economic crisis being experienced by Spain, which disclosed the causes (sources), its consequences (outcomes) and measures taken by governments to get out of this economic, financial crossroads and publishes analyzes, similar situation that is hurting the rest of the European community. Situation arising from a series of ambitious government plans and speculation of a booming economy, that involved all sectors both public and private.